PLACE OF THE SPANISH LANGUAGE IN THE OV / VO TYPOLOGY - S. N. Bezus (Гуманитарные и юридические исследования)
There are different classifications of languages. Structural-typological approach to the classification of languages is based on a comparison of the word order, i.e. the position of main and secondary components in the sentences. The paper provides an overview of the main theories of language typology, which are based on the order of the basic components of the sentences: subject (S), verb (V) and object (O). In particular, it examines the place of the Spanish language in the classification of languages with the basic order OV or VO. The author gives the review of classical theories (according to which Spanish is traditionally considered SVO-language), and new investigations in this area, in which the Spanish language is considered VSO-language.